2012
DOI: 10.1097/tp.0b013e3182637054
|View full text |Cite
|
Sign up to set email alerts
|

Subzero 24-hr Nonfreezing Rat Heart Preservation

Abstract: The rat hearts preserved in a variable magnetic field at -3°C showed better hemodynamic and metabolic performance than those preserved using conventional storage at 4°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…To enhance the current quality of donor hearts, researchers continue to experiment with various methods in animals. For example, improvement of the UW solution18, a two-layer method using UW19, and super cooling with UW20 have all been attempted. These attempts have resulted in the stock solution having organ- and/or cell-protective effects because immersion in a stock solution is generally considered important to organ preservation1011.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the current quality of donor hearts, researchers continue to experiment with various methods in animals. For example, improvement of the UW solution18, a two-layer method using UW19, and super cooling with UW20 have all been attempted. These attempts have resulted in the stock solution having organ- and/or cell-protective effects because immersion in a stock solution is generally considered important to organ preservation1011.…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al . [19] reported that rat hearts preserved in a variable magnetic field at -3°C for 24 hours exhibited satisfactory hemodynamic and metabolic performance. Preservation as described above only reduces the metabolic needs of tissues, and is thus not suitable for long-term storage.…”
Section: Discussionmentioning
confidence: 99%
“…Modern cryobiological theory holds that the most dangerous temperature zone during cryopreservation is 0 to -60°C, especially 0 to -10°C, because intercellular ice accumulates at these temperatures and cell damage occurs within this temperature zone during the process of cooling or thawing [3,19,27]. Moreover, it has been reported that thawing too slowly induces recrystallization of the intercellular ice, which results in fatal injury to the cell [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slowing down metabolism and reducing high ATP consumption appears to be a key mechanism of cold storage and appears to be improved during supercooling. Preservation of organ energy status during supercooling has been confirmed in lungs (57) and hearts (58,59), where short-term supercooling preservation has been successfully performed, but transplantation has not been attempted.…”
Section: Supercoolingmentioning
confidence: 99%